Height profile variations of ionospheric conductivity: A case study in Addis Ababa, Ethiopia - Endeshaw, Lake (Himalayan Physics, 2024)
Ionospheric conductivity is the ability to conduct ionospheric current and is impacted by a variety of current system flows in height profiles, which increase ionosphere conductivity. In this study, we have analyzed the height profiles of the ionospheric conductivity daily and monthly variations in Addis Ababa, Ethiopia, during a very low solar activity phase in the year 2020. The daily height profile variations of ionospheric conductivity in Addis Ababa with geographic latitude 9o N and longitude 39o E are estimated at midnight (00:00 UT), morning (09:00 UT), mid-day (12:00 UT), and early nighttime (18:00 UT). The monthly variations of ionospheric conductivity (parallel, Pedersen, and Hall conductivity) are also presented for all months, with the highest ionospheric variability occurring after noon (14.00 UT). At midnight (00:00 UT) and early nighttime (18:00 UT), the ionospheric conductivity shows more fluctuation than in the morning (09:00 UT) and midday (12:00 UT) in diurnal variation. The monthly variations of ionospheric conductivity (parallel, Pedersen, and Hall conductivity) in the daytime at 14:00 UT increase steeply to reach their peak values and keep the sharpness of their variability.